The Need for Provision of Social Assistance to Kiai Pondok Pesantren in the Covid-19 Pandemic - Edy Effendi; Suyono Suyono; Amin Hidayat (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2020)
The Covid-19 pandemic has had a serious impact in almost all fields, including Islamic boarding schools and their owners, kiai. The government has helped Islamic boarding schools as institutions, but not to kiai personally. This study aims to provide answers to whether or not it is necessary to provide social assistance to kiai personally, so that it can be used as input to stakeholders. This study uses the Regulatory Impact Assessment (RIA) method, analyzing the aspects of the benefits and costs of providing social assistance to kiai and how these two things touch based on the perceptions of expert opinion. Data processing was carried out based on the results of a questionnaire conducted using the Analytical Hierarchy Process (AHP) model which was distributed to expert respondents. The results of the study indicate that it is necessary to provide social assistance to kiai personally.